HUBUNGAN PERAWATAN PAYUDARA IBU PADA MASA POST PARTUM DENGAN MENYUSUI EKSKLUSIF DI PUSKESMAS ULU MORO’O NIAS BARAT TAHUN 2022 - Gulo, Hendrika Hartati; Novita, Regina Vidya Trias; Simbolon, Anna Rejeki (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
The WHO recommends that exclusive breastfeeding for six months must be carried out worldwide because it has benefits for both mother and baby, and is the baby's right to get breast milk. This study aims to determine whether there is a relationship between maternal breast care in the postpartum period and exclusive breastfeeding at the Ulu Moro'o Health Center, West Nias. This research is a quantitative study using an analytic design with a cross-sectional approach. The number of 60 respondents is based on the Slovin formula, with a total sampling in December 2021. Data collection uses a questionnaire about characteristics and breast care. The results showed that the majority (90%) were female reproductive age 20-35 years old, household work (91.7%), multiparous (61.7%), normal delivery (90%), and breastfeeding history was not the first experience (78.3%). The results of the chi-square test showed that there was no relationship between breast care (massage p= 0.467; warm or cold compresses p= 0.601) of mothers during the postpartum period with exclusive breastfeeding, so it was concluded that breastfeeding problems could not only be overcome by breast care such as massage or breastfeeding. However, it requires the cooperation of health workers in making skin-to-skin contact and IMD which is the first step in maintaining breastfeeding. The Puskesmas is expected to provide alternatives or other methods of breast care as well as education at least twice during pregnancy to mothers according to government regulations and intensive assistance to mothers in carrying out breast care education.